2015
DOI: 10.1016/j.atmosenv.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble ions and trace elements in surface snow and their potential source regions across northeastern China

Abstract: h i g h l i g h t sWe collected 92 snow samples from 13 sites across northeastern China. The snow in the remote northeast on the border near Siberia was extremely clean. Al, and Fe were primarily derived from natural sources. Cu, Zn, As, V, and Cd in snow samples were likely derived from anthropogenic sources. a b s t r a c tWe collected 92 snow samples from 13 sites across northeastern China from January 7 to February 15, 2014. The surface snow samples were analyzed for the major water-soluble ions (SO 2À 4 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 56 publications
(75 reference statements)
1
37
0
Order By: Relevance
“…Major water-soluble ions and trace elements in surface snow samples during this snow survey have already been investigated by Wang et al (2015). However, the importance of ILAPs in seasonal snow during this survey has not been discussed yet, which will be addressed below.…”
Section: Chemical Speciationmentioning
confidence: 99%
See 2 more Smart Citations
“…Major water-soluble ions and trace elements in surface snow samples during this snow survey have already been investigated by Wang et al (2015). However, the importance of ILAPs in seasonal snow during this survey has not been discussed yet, which will be addressed below.…”
Section: Chemical Speciationmentioning
confidence: 99%
“…The fraction of sea salt was found to range from 6.3 to 20.9 %. Wang et al (2015) showed that higher Cl − / Na + ratios in seasonal snow found in the 2014 Chinese survey were 1-2 times greater than those of seawater, implying that they constituted a significant source of anthropogenic Cl − .…”
Section: Contributions To Light Absorption By Ilapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginoux et al (2010) estimated that anthropogenic dust accounts for 25% of all dust aerosols using 10 observational data from MODIS (Moderate Resolution Imaging Spectroradiometer) Deep Blue satellite products combined with a land-use fraction dataset. Anthropogenic dust primarily originates from urban and regional sources, especially during the winter; this dust is commonly enriched in heavy metals and other toxic elements (Kamani et al, 2015;Li et al, 2013;Wang et al, 2015;. Northeastern China 15 and its surrounding regions are generally regarded as industrial areas that are most strongly affected by human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the potential impacts of anthropogenic soil dust have also received an increasing amount of attention (Prospero et al, 2002;Huang et al, 2015a;Tegen and Fung, 1995;Tegen et al, 2002;Shi et al, 2015;Pu et al, 2015;Wang et al, 2015). 5…”
Section: Introductionmentioning
confidence: 99%